PENGARUH PENDEKATAN MULTIREPRESENTASI TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK PADA MATERI MOMENTUM DAN IMPULS - Wati, Gita; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractAn objective of this study was to investigate the effect of multiple representations approach in learning physics to the cognitive skills of students at SMA Negeri 1 Anjongan on momentum and impuls. The form of research used quasi-experimental design with pretest-posttest control group design. The saturation sampling technique was used to investigate the sample. The sample was two classes with one class as an experimental class and one class as a control class. This study used 5 question essays as an instrument to measure students’cognitive skills in the pretest-posttest while responses of student about multiple representations are used a questionnaire. The results of data showed that the increase in cognitive skillss of the experimental class students obtained N-Gain value of 0.44 which was categorized as moderate and in the control class the value of the N-Gain of 0.23 was categorized as low. The statistical test ( =-5.89) showed that there are differences in cognitive skills of students (α= 5%) between students who are given learning with a multiple representations approach and students who are given learning with the usual learning approach. Students gave high response about the learning multiple representations with a percentage of the total response 82.23%. Keywords: Cognitive Skills, Momentum And Impuls, Multiple representations Approach